Down and Out. - Lezard, Nicholas (New Statesman, 2016)
A personal narrative is presented in which the author reflects on traveling to Switzerland to attend a meeting and a festival and talks about how various hi-jinks when he worked at British Telecom in the 1980s using the interoffice communication system of people who left their computers unattended.